Silver-coated nickel low-temperature silver paste and preparation method and application thereof
By developing silver-clad nickel-clad low-temperature silver paste, using the combination of blocked polyisocyanate and curing accelerator, rapid curing at low temperatures is achieved, and by reducing costs by using silver-clad nickel powder, traditional high-temperature silver paste has been solved by solving the high energy consumption and heterojunction solar energy in traditional high-temperature silver paste The problem of high cost of low-temperature silver paste in the battery has achieved low energy consumption and low cost silver paste preparation.
Patent Information
- Application Number
- CN202411691991.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The high-temperature silver paste used in traditional solar cells leads to high energy consumption, and the low-temperature silver paste of heterojunction solar cells is relatively high, affecting its widespread application.
A silver-clad nickel-clad low-temperature silver paste was developed, and cured within 30 minutes of below 190-200°C by combining a blocked polyisocyanate and a curing accelerator, and the production cost was reduced by replacing part of the silver-clad nickel powder.
The low-temperature silver paste can cure quickly under low temperature conditions, reducing energy consumption during battery production, while maintaining good electrical performance, meeting the use needs of silicon heterojunction solar cells, and reducing production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a low-temperature silver paste and a preparation method and application thereof. Background Art
[0002] In the past decade, clean energy production methods such as photovoltaics and wind power have gradually emerged. Especially in recent years, with the country's emphasis on new energy, more and more resources have been invested in the development of technologies to improve the conversion efficiency of solar cells. Although the cell conversion efficiency of traditional monocrystalline silicon solar cells has reached 22-23%, it is difficult to further improve the photoelectric conversion efficiency due to its own structure. In addition, the silver paste used in traditional solar cells requires high-temperature sintering above 700°C, which requires relatively large energy consumption. Heterojunction solar cells, as a new type of high-efficiency solar cell structure, are attracting industry attention. In October 2021, according to the official microblog of Longi Co., Ltd., its commercial-size HJT (M6 silicon-based heterojunction) solar cells were tested by the Institute for Solar Energy Research Hamelin (ISFH) in Germany, with a conversion efficiency of 25.82%, breaking the world record. Moreover, the heterojunction cell paste is a low-temperature curing type, so heterojunction is the next generation technology with the most potential to replace traditional solar cells. However, heterojunction solar cells also face large initial investments, especially silver paste, which accounts for 25% of the total cost of the battery. Therefore, reducing the cost of low-temperature silver paste for heterojunction batteries is an issue that urgently needs to be addressed in the industry.
[0003] Low-temperature silver paste is mainly composed of conductive functional phase (silver powder, silver-coated copper powder), bonding phase (resin organic polymer), a small amount of additives (dispersant, leveling agent, thixotropic agent, adhesion promoter, etc.) and organic solvent. Different from traditional conductive silver paste, low-temperature curing silver paste does not use glass phase, the sintering temperature is greatly reduced, and the silver powder is connected by resin bonding phase. The low-temperature curing condition meets the process requirements of HJT solar cells, but it has a certain impact on the conductivity of the paste. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the embodiment of the present invention provides a silver-coated nickel low-temperature silver paste that can be cured within 30 minutes at a temperature below 190-200°C while maintaining good electrical properties to meet the use requirements of silicon heterojunction batteries.
[0005] The silver-coated nickel low-temperature silver paste of the embodiment of the present invention includes 0.5-3wt% of blocked polyisocyanate, 1-4wt% of epoxy resin, 0.05-0.1wt% of curing accelerator, 45-83wt% of silver powder, 10-50wt% of silver-coated nickel powder and 2-8wt% of solvent.
[0006] The advantages and technical effects brought by the silver-coated nickel low-temperature silver paste of the embodiment of the present invention are as follows: 1. In the embodiment of the present invention, blocked polyisocyanate is used as a curing agent, and a certain amount of curing accelerator is added at the same time, so that the low-temperature silver paste can be cured within 30 minutes at 190-200°C, thereby reducing the energy consumption in the battery production process; 2. In the embodiment of the present invention, silver-coated nickel powder is used to replace part of the silver powder, which can not only reduce the production cost of the low-temperature silver paste, but also the silver-coated nickel powder has the advantages of good electrical and thermal conductivity, good dispersibility, good oxidation resistance, etc., which can ensure that the produced low-temperature silver paste has good performance; 3. In the embodiment of the present invention, by selecting various substances and limiting their usage within a suitable range, the low-temperature silver paste can have good electrical properties and meet the use requirements of silicon heterojunction solar cells.
[0007] In some embodiments, the epoxy resin includes at least one of bisphenol F epoxy resin, bisphenol A epoxy resin, resorcinol formaldehyde epoxy resin, or polycyanurate triglyceride epoxy resin.
[0008] In some embodiments, the silver powder includes spherical silver powder and flake silver powder.
[0009] In some embodiments, the spherical silver powder has an average particle size of 0.1 to 0.8 μm and a tap density of 4 to 7 g / cm3;
[0010] And / or, the average particle size of the flaky silver powder is 2 to 5 μm, and the tap density is 4 to 7 g / cm3.
[0011] In some embodiments, the mass ratio of the spherical silver powder to the flake silver powder is 1:1 to 1:4.
[0012] In some embodiments, the silver-coated nickel powder is a spherical silver-coated nickel powder, the average particle size of the silver-coated nickel powder is 0.30 to 1.0 μm, and the tap density is >3.5 g / cm3;
[0013] And / or, the silver content in the silver-coated nickel powder is 5-55wt%.
[0014] In some embodiments, the curing accelerator includes at least one of an imidazole compound or a boron trifluoride ethylamine complex;
[0015] And / or, the solvent includes at least one of terpineol, diethylene glycol butyl ether acetate or dipropylene glycol.
[0016] The embodiment of the present invention also provides a method for preparing a silver-coated nickel low-temperature silver paste, comprising the following steps:
[0017] (1) mixing a solvent and a phenolic resin under magnetic stirring to obtain a first mixture;
[0018] (2) mixing the first mixture obtained in step (1) with epoxy resin in a double planetary mixer, and then adding silver powder, silver-coated nickel powder and a curing accelerator to mix, to obtain a second mixture;
[0019] (3) The second mixture obtained in step (2) is dispersed on a three-roll mill, and then filtered and de-bubbled.
[0020] In some embodiments, in step (2), the mixing temperature in the double planetary mixer is 0 to 30° C.;
[0021] And / or, in the step (3), the number of dispersion times on the three-roll mill is 3 to 5 times.
[0022] The embodiments of the present invention also provide the use of the above-mentioned silver-coated nickel low-temperature silver paste or the silver-coated nickel low-temperature silver paste prepared by the above-mentioned preparation method in a silicon heterojunction battery. DETAILED DESCRIPTION
[0023] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0024] The silver-plated nickel low-temperature silver paste of the embodiment of the present invention includes 0.5-3wt% of phenolic resin, 1-4wt% of epoxy resin, 0.05-0.1wt% of curing accelerator, 85-93wt% of silver powder and 2-8wt% of solvent.
[0025] The silver-coated nickel low-temperature silver paste of the embodiment of the present invention adopts blocked polyisocyanate as a curing agent, and a certain amount of curing accelerator is added at the same time, so that the low-temperature silver paste can be cured within 30 minutes at 190-200°C, thereby reducing the energy consumption in the battery production process; in the embodiment of the present invention, silver-coated nickel powder is used to replace part of the silver powder, which can not only reduce the production cost of the low-temperature silver paste, but also the silver-coated nickel powder has the advantages of good electrical and thermal conductivity, good dispersibility, good oxidation resistance, etc., which can ensure that the produced low-temperature silver paste has good performance; in the embodiment of the present invention, by selecting various substances and limiting their usage within a suitable range, the low-temperature silver paste can have good electrical and mechanical properties, meeting the use requirements of silicon heterojunction solar cells.
[0026] In some embodiments, preferably, the epoxy resin includes at least one of bisphenol F epoxy resin, bisphenol A epoxy resin, resorcinol formaldehyde epoxy resin or polycyanurate triglyceride epoxy resin.
[0027] In some embodiments, preferably, the silver powder includes spherical silver powder and flake silver powder.
[0028] In the embodiment of the present invention, the silver powder is defined as a mixture of spherical silver powder and flaky silver powder. The spherical silver powders are in point-to-point contact with each other, have fluidity and rheology, and have good printing adaptability. The flaky silver powders are in surface or line contact with each other, which can improve the conductivity of the silver paste. The silver powder is formed by a mixture of spherical silver powder and flaky silver powder, and the spherical silver powder with a small diameter is used to fill the gaps in the flaky silver powder, further improving the density of the silver paste, and it is defined to have a higher tap density, so that the silver paste can reach a silver content of >90%.
[0029] In some embodiments, preferably, the average particle size of the spherical silver powder is 0.1 to 0.8 μm, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, etc.; the tap density is 4 to 7 g / cm 3 ; For example 4g / cm 3 , 4.5g / cm 3 , 5g / cm 3 , 5.5g / cm 3 , 6g / cm 3 、6.5g / cm 3 , 7g / cm 3 wait.
[0030] In some embodiments, preferably, the average particle size of the flaky silver powder is 2 to 5 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc.; the tap density is 4 to 7 g / cm 3 , for example 4g / cm 3 , 4.5g / cm 3 , 5g / cm 3 , 5.5g / cm 3 , 6g / cm 3 、6.5g / cm 3 , 7g / cm 3 wait.
[0031] In some embodiments, preferably, the mass ratio of the spherical silver powder to the flake silver powder is 1:1 to 1:4, for example, 1:1, 1:1.5, 1:2.0, 1:2.5, 1:3.0, 1:3.5, 1:4, etc.
[0032] In the embodiment of the present invention, the mass ratio of spherical silver powder and flaky silver powder is optimized, so that the low-temperature silver paste can have good printing adaptability and conductivity at the same time; if the amount of spherical silver powder is too much, the conductivity of the silver paste will be reduced; if the amount of spherical silver powder is too little, the printing adaptability of the silver paste will be deteriorated.
[0033] In some embodiments, preferably, the silver-coated nickel powder is a spherical silver-coated nickel powder, and the average particle size of the silver-coated nickel powder is 0.30-1.0 μm, for example, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.1 μm, etc.; the tap density is >3.5 g / cm 3 , for example 3.6 g / cm 3 、3.8g / cm 3 , 4.0g / cm 3 , 4.2g / cm 3 4.4g / cm 3 , 4.6g / cm 3 , 5.0g / cm 3 , 5.2g / cm 3 , 5.4g / cm 3 , 5.6g / cm 3 , 5.8g / cm 3 Etc. The appropriate particle size and tap density can increase the paste density in low-temperature silver paste and play a good filling role.
[0034] In some embodiments, preferably, the silver content in the silver-coated nickel powder is 5-55wt%, for example, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, etc.
[0035] In some embodiments, preferably, the curing accelerator includes at least one of an imidazole compound or a boron trifluoride ethylamine complex.
[0036] In the embodiment of the present invention, the type of curing accelerator is preferably selected. The curing accelerator of this type can form a synergistic effect with the phenolic resin curing agent to improve the low-temperature curing performance of the silver paste.
[0037] In some embodiments, preferably, the solvent includes at least one of terpineol, diethylene glycol butyl ether acetate or dipropylene glycol. In the embodiments of the present invention, there is no need to specifically limit the solvent, as long as it can effectively dissolve the substance.
[0038] The embodiment of the present invention also provides a method for preparing a silver-coated nickel low-temperature silver paste, comprising the following steps:
[0039] (1) mixing a solvent and a phenolic resin under magnetic stirring to obtain a first mixture;
[0040] (2) mixing the first mixture obtained in step (1) with epoxy resin in a double planetary mixer, and then adding silver powder, silver-coated nickel powder and a curing accelerator to obtain a second mixture;
[0041] (3) The second mixture obtained in step (2) is dispersed on a three-roll mill, and then filtered and de-bubbled.
[0042] In some embodiments, preferably, in step (2), the mixing temperature in the double planetary mixer is 0 to 30°C;
[0043] And / or, in the step (3), the number of dispersion times on the three-roll mill is 3 to 5 times.
[0044] The embodiments of the present invention also provide the use of the above-mentioned silver-coated nickel low-temperature silver paste or the silver-coated nickel low-temperature silver paste prepared by the above-mentioned preparation method in a silicon heterojunction battery.
[0045] The technical solution of the present invention is described in detail below in conjunction with specific embodiments.
[0046] Example 1
[0047] (1) Weigh 2.52 g of blocked polyisocyanate into a beaker, add 21.88 g of diethylene glycol butyl ether acetate, place in a magnetic stirrer and heat to 60° C. in a constant temperature water bath, stir continuously at a speed of 600 r / min until the phenolic resin is completely dissolved, keep warm for 1 hour after complete dissolution, cool and keep for later use, to obtain a first mixture:
[0048] (2) The first mixture and 18g of Taiwan Changchun bisphenol F epoxy resin BFE-170 were then stirred at 20°C by double planetary stirring, and 337.6g of silver powder, 100g of silver-coated nickel powder and 0.4g of imidazole compound were added under stirring. The silver powder includes spherical powder and flaky silver powder, wherein the spherical silver powder has an average particle size of 0.80μm and a tap density of 4.3g / cm 3 The average particle size of the flaky silver powder is 4.08 μm, and the tap density is 6.67 g / cm 3 The weight ratio of spherical silver powder to flake silver powder is 1:2. The average particle size of silver-coated nickel powder is 0.4 μm and the tap density is 4.8 g / cm 3 , the content of silver in the silver-coated nickel powder is 25wt%;
[0049] (3) Then, the mixture is dispersed three times on a three-roll disperser and filtered and treated to remove bubbles to obtain a silver-coated nickel low-temperature silver paste for silicon heterojunction solar cells.
[0050] Example 2
[0051] (1) Weigh 7.56 g of blocked polyisocyanate into a beaker, add 17.84 g of terpineol, place in a magnetic stirrer and heat to 70° C. in a constant temperature water bath, stir continuously at a speed of 800 r / min until the phenolic resin is completely dissolved, keep warm for 1 hour after complete dissolution, cool and keep for later use, to obtain a first mixture;
[0052] (2) The first mixture and 11.22g of Nan Ya bisphenol F epoxy resin NPEF-170 were then stirred at 25°C by double planetary stirring, and 350g of silver powder, 100g of silver-coated nickel powder and 0.3g of imidazole compound were added under stirring. The silver powder includes spherical powder and flaky silver powder, wherein the spherical silver powder has an average particle size of 0.5μm and a tap density of 4.9g / cm 3 The average particle size of the flaky silver powder is 3.56μm, and the tap density is 5.56g / cm 3 The weight ratio of spherical silver powder to flake silver powder is 1:1. The average particle size of silver-coated nickel powder is 0.7 μm and the tap density is 5.3 g / cm 3 The silver content in the silver-coated nickel powder is 25wt%.
[0053] (3) Then, the mixture is dispersed three times on a three-roll disperser and filtered and treated to remove bubbles to obtain a silver-coated nickel low-temperature silver paste for silicon heterojunction solar cells.
[0054] Example 3
[0055] (1) Weigh 5.14 g of blocked polyisocyanate into a beaker, add 16.76 g of dipropylene glycol, place in a magnetic stirrer and heat to 70° C. in a constant temperature water bath, stir continuously at a speed of 700 r / min until the phenolic resin is completely dissolved, keep warm for 1 hour after complete dissolution, cool and keep for later use, to obtain a first mixture;
[0056] (2) The first mixture and 12.48g of Nan Ya bisphenol F epoxy resin NPEF-170 were then stirred at 25°C by double planetary stirring, and 240g of silver powder, 200g of silver-coated nickel powder and 0.4g of boron trifluoride ethylamine complex were added under stirring. The silver powder includes spherical powder and flaky silver powder, wherein the spherical silver powder has an average particle size of 0.2μm and a tap density of 5.7g / cm 3 The average particle size of the flaky silver powder is 4.56μm, and the tap density is 4.16g / cm 3 The weight ratio of spherical silver powder to flake silver powder is 1:1. The average particle size of silver-coated nickel powder is 0.6 μm and the tap density is 3.9 g / cm 3 The silver content in the silver-coated nickel powder is 37wt%.
[0057] (3) Then, the mixture is dispersed three times on a three-roll disperser, filtered, and the bubbles are removed to obtain a silver-coated nickel low-temperature silver paste for silicon heterojunction solar cells.
[0058] Comparative Example 1
[0059] The preparation method of this comparative example is the same as that of Example 1, except that in step (1), no silver-coated nickel powder is added and the amount of silver powder added is 437.6 g.
[0060] Comparative Example 2
[0061] The preparation method of this comparative example is the same as that of Example 1, except that in step (1), 0.4 g of imidazole compound is not added.
[0062] The performance of the silver-clad nickel low-temperature silver pastes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested, and the results are shown in Table 1:
[0063] Table 1
[0064]
[0065] The low-temperature silver pastes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were used to prepare silicon heterojunction solar cells, and the performance of the cells was tested. The results are shown in Table 2:
[0066] Table 2
[0067] [Isc(A)] <![CDATA[[Jsc(mA / cm 2 )]]]> [Voc(V)] [FF(%)] [Eff(%)] Example 1 9.3684 38.33 0.7409 83.24 23.64 Example 2 9.2987 38.06 0.7381 81.02 22.76 Example 3 9.3150 38.11 0.7392 83.26 23.45 Comparative Example 1 9.3255 38.17 0.7412 83.84 23.72 Comparative Example 2 9.3454 38.46 0.7154 82.47 23.54
[0068] Note: Isc refers to the short-circuit current of the battery, Jsc refers to the short-circuit current density of the battery, Voc refers to the open-circuit voltage of the battery, FF refers to the fill factor of the battery, and Eff refers to the conversion efficiency of the battery.
[0069] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0070] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A silver-coated nickel low-temperature silver paste, characterized in that: The invention comprises 0.5-3wt% of blocked polyisocyanate, 1-4wt% of epoxy resin, 0.05-0.1wt% of curing accelerator, 45-83wt% of silver powder, 10-50wt% of silver-coated nickel powder and 2-8wt% of solvent.
2. The silver-clad nickel low-temperature silver paste according to claim 1, characterized in that: The epoxy resin includes at least one of bisphenol F epoxy resin, bisphenol A epoxy resin, resorcinol formaldehyde epoxy resin or polycyanurate triglyceride epoxy resin.
3. The silver-clad nickel low-temperature silver paste according to claim 1, characterized in that: The silver powder includes spherical silver powder and flake silver powder.
4. The silver-clad nickel low-temperature silver paste according to claim 3, characterized in that: The average particle size of the spherical silver powder is 0.1 to 0.8 μm, and the tap density is 4 to 7 g / cm3; And / or, the average particle size of the flaky silver powder is 2 to 5 μm, and the tap density is 4 to 7 g / cm3.
5. The silver-clad nickel low-temperature silver paste according to claim 3 or 4, characterized in that: The mass ratio of the spherical silver powder to the flaky silver powder is 1:1 to 1:
4.
6. The silver-clad nickel low-temperature silver paste according to claim 1, characterized in that: The silver-coated nickel powder is spherical, has an average particle size of 0.30 to 1.0 μm, and a tap density of >3.5 g / cm3; And / or, the silver content in the silver-coated nickel powder is 5-55wt%.
7. The silver-clad nickel low-temperature silver paste according to claim 1, characterized in that: The curing accelerator includes at least one of an imidazole compound or a boron trifluoride ethylamine complex; And / or, the solvent includes at least one of terpineol, diethylene glycol butyl ether acetate or dipropylene glycol.
8. The method for preparing silver-coated nickel low-temperature silver paste according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) mixing a solvent and a phenolic resin under magnetic stirring to obtain a first mixture; (2) mixing the first mixture obtained in step (1) with epoxy resin in a double planetary mixer, and then adding silver powder, silver-coated nickel powder and a curing accelerator to mix, to obtain a second mixture; (3) The second mixture obtained in step (2) is dispersed on a three-roll mill, and then filtered and de-bubbled.
9. The method for preparing the silver-clad nickel low-temperature silver paste according to claim 8, characterized in that: In the step (2), the mixing temperature in the double planetary mixer is 0 to 30° C.; And / or, in the step (3), the number of dispersion times on the three-roll mill is 3 to 5 times.
10. Use of the silver-coated nickel low-temperature silver paste according to any one of claims 1 to 7 or the silver-coated nickel low-temperature silver paste prepared by the preparation method according to claim 8 or 9 in silicon heterojunction batteries.